SGLT2 inhibition mitigates intracerebral hemorrhage risk by modulating inflammation - Mingsheng Huang; Yiheng Liu; Cheng Chen (Scientific Reports)
Abstract Sodium-glucose cotransporter 2 (SGLT-2) inhibitors have been increasingly recognized for their potential neuroprotective properties. Nevertheless, their effects on intracerebral hemorrhage (ICH) are still debated, with the precise mechanisms involved remaining unclear. Recent studies indicate that these inhibitors might lower ICH risk through anti-inflammatory mechanisms. This study analyzed genome-wide association study (GWAS) data from individuals of European ancestry, focusing on the relationship between 92 inflammatory biomarkers and ICH. A two-sample, two-step Mendelian randomization (MR) approach was used to examine the potential connection between SGLT-2 inhibition and ICH, as well as to investigate whether inflammatory biomarkers mediate this relationship. Genetic proxies for SGLT-2 inhibition were determined based on variants linked to the expression of the SLC5A2 gene and levels of glycated hemoglobin (HbA1c). Odds ratios with 95% confidence intervals were calculated to assess the associations between SGLT-2 inhibition, inflammatory biomarkers, and the likelihood of ICH. The genetic prediction of SGLT-2 inhibition was found to be inversely related to the risk of ICH (OR = 0.152; 95% CI = 0.066–0.352; P < 0.001). Out of the 92 inflammatory biomarkers examined, 33 showed a significant association with SGLT-2 inhibition. Notably, levels of IL10 receptor subunit beta (IL10RB) were significantly correlated with both SGLT-2 inhibition and ICH. Moreover, IL10RB accounted for 9.167% of the total mediation effect of SGLT-2 inhibition on ICH. The findings of this study suggest a link between SGLT-2 inhibition and a decreased risk of ICH, with IL10RB emerging as a possible mediator. This presents a potential new strategy for ICH prevention and intervention. Further studies are needed to clarify the role of inflammatory pathways in the connection between SGLT-2 inhibition and ICH.